ABOUT SOME QUESTIONS ARISING AT APPLICATION OF STANDARD RESOLUTIONS OF THE SUPREME COURT - Umarov Сапархан Суюндикович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
This article addresses the issue of the legal nature of normative decisions of the Plenum of the Supreme Court of the Republic of Kazakhstan on the practice of law, based on pooled data of judicial practice.